The correlation analysis and research progress of the protection of optic nerve in glaucoma - HANDandan; LIJingmin (眼科学报; 卷 31, 编号 1 (March 2016): 《眼科学报》, 2016)
Glaucoma is an irreversible eye disease with the characteristic of optic nerve damage and visual field defect, the clinical manifestation is behaved for vision loss, eye pain with symptoms such as headache, which rate of blindness ranks second place. The optic nerve injury of glaucoma has a certain genetic predisposition. There are many risk factors result in optic nerve atrophy and visual field defect, one of the major causes of blindness including optic ganglion damage, pathological elevation of intraocular pressure. So on the one hand in the treatment of glaucoma should be considered to reduce intraocular pressure, on the other hand, to protect the optic nerve. This article will reviews the mechanism, influencing factors, classification methods, optic nerve related detection indexes and clinical application and treatment of optic nerve injury.